The layers of inequality in paid domestic labour: a global study on domestic workers and precarious work - Jokela, Merita (fi=Turun yliopisto|en=University of Turku|, 2018)
Abstract: This dissertation examines inequalities in paid domestic labour from a global comparative perspective. I approach the subject through three different layers that represent the factors identified in previous studies as shaping paid domestic labour and the position of domestic workers in the labour markets: 1) the structural layer that refers to the socio-demographic developments and structural mechanisms in the society, 2) the individual layer that includes the characteristics of persons working in domestic service and the occupation, and 3) the policy layer that comprises the political economy of paid domestic labour and the policies influencing the employment of domestic workers. The dissertation consists of three international peer reviewed articles that each tackles one of the layers from a comparative perspective. For the empirical analyses three types of data are used: international databases of macro-level indicators (World Bank, International Labour Organization), micro-level survey data (Luxembourg Income Study) and policy documents. In recent years, paid domestic labour, that is, household work that is performed in private households has become a widely studied subject in social sciences particularly in research related to gender, care and migration. Currently, domestic service is promoted across countries not only as a way for upper and middle income households to reconcile with work and family life but also, as one of the growing sectors of employment that is supposed to provide job opportunities particularly for women, lower educated individuals and migrants. The results of the first article, a quantitative comparison of 74 countries, show that higher income inequality within countries and higher proportion of migrants in a country are associated with higher prevalence of paid domestic labour. The five-country comparison of the second article demonstrates that precarious employment conditions (measured here by part-time employment, low wages, short job tenure, and unemployment experience) are more prevalent in paid domestic work compared to other industries. Furthermore, the results show that across welfare regimes, working in the paid domestic sector increases the risk of working in precarious employment settings. The results of the third article covering domestic employment policies in OECD countries show that policies related to domestic service may have a significant impact on the dynamics of the sector and the precariousness of workers’ employment, and how welfare states across world regulate (or disregard regulations) the sector of domestic services reflects the position of domestic workers in these labour markets. Thus, the three different layers – structural, individual, and policy – intersect in ways that contribute to maintaining the ‘special’ position of domestic workers across countries: the cultural undervaluation of domestic work, together with a strongly feminised workforce that consists predominantly of migrants, places domestic workers at greater risk of working under precarious employment conditions. Moreover, in many countries insufficient care provisions and general legitimisation of domestic workers’ weaker employment conditions drive households to turn to private domestic and care services. The precarity of paid domestic labour derives partly from the multiple disadvantaged social categories of the persons working in the sector. Paradoxically, the reasons for the inequalities (gender, “race”, class, cultural background or nationality) in domestic service are the same factors that account for their employment in the first place. The issue of domestic workers’ remuneration and employment conditions remains problematic, as it is directly linked to households’ abilities to pay for these services. Particularly in countries where domestic workers are employed on a full-time basis and fill gaps in public care provisions, this poses a real challenge if households do not receive support from the state. Thus, as paid domestic labour in the 21st century now seems to be living its new era through globalisation and as part of the neoliberal organisation of care, questions related to domestic workers’ status and working conditions again become topical across the globe.

Tiivistelmä: Tutkimuksessani tarkastelen palkattua kotitaloustyötä ja siihen kytkeytyvää eriarvoisuutta globaalista näkökulmasta. Tutkin tekijöitä, jotka vaikuttavat palkatun kotitaloustyön markkinoihin sekä alalla työskentelevien työntekijöiden asemaan. Analysoin näitä tekijöitä kolmen eri kategorian kautta, joita tässä tutkimuksessa kutsun kerrostumiksi: 1) rakenteiden kerrostuma viittaa sosiodemografisiin kehityssuuntiin ja yhteiskunnan mekanismeihin, 2) yksilöiden kerrostuma, eli kotitaloustyöhön ja alan työntekijöihin liittyvät ominaisuudet, sekä 3) politiikan kerrostuma, joka sisältää palkattuun kotitaloustyöhön kohdistetut poliittiset toimet. Väitöskirjani koostuu kolmesta kansainvälisestä vertaisarvioidusta artikkelista, joista jokainen käsittelee yhtä eriarvoisuuden kerrostumaa vertailevasta näkökulmasta. Tutkimuksessani hyödynnän kolmea erityyppistä aineistoa, joita ovat kansainvälisten tietovarantojen (Maailmanpankki, Kansainvälinen työjärjestö) makrotason indikaattorit, mikrotason survey-ainestot (Luxembourg Income Study) sekä poliittisen päätöksenteon tueksi laaditut asiakirjat ja raportit. Kiinnostus palkattuun kotitaloustyöhön, eli kotitalouksissa suoritettavaan kotityöhön, on viime vuosina kasvanut merkittävästi sosiaalitieteen alan tutkijoiden keskuudessa etenkin sukupuolta, hoivatarpeita sekä maahanmuuttoa koskevassa tutkimuksessa. Kotitaloustyöntekijöitä on pidetty yhtenä ratkaisuna työn ja perheen yhteensovittamiseen varsinkin ylempi- ja keskiluokkaisissa perheissä. Palkatun kotitaloustyön sanotaan usein olevan yksi nopeimmin kasvavista toimialoista, jonka on tarkoitus luoda työpaikkoja ennen kaikkea naisille, matalasti koulutetuille ja maahanmuuttajille. Väitöskirjani ensimmäisen artikkelin tulokset, jotka perustuvat 74 maan tilastolliseen vertailuun, osoittavat että korkeampi taloudellinen eriarvoisuus ja maahanmuuttajien korkeampi osuus väestöstä on yhteydessä kotitaloustyöntekijöiden suurempaan osuuteen työvoimasta. Toisen artikkelin viiden maan kvantitatiivinen vertailu vahvistaa, että työn prekaarius (työn osa-aikaisuus, matala palkka, työn kesto ja työttömyyden kokeminen) on yleisempää kotitaloustyöntekijöiden keskuudessa verrattuna muilla toimialoilla työskenteleviin. Tulosten mukaan kotitaloustyötä tekevillä on suurempi riski työskennellä prekaareissa työoloissa hyvinvointivaltioregiimistä riippumatta. OECD-maiden palkatun kotitaloustyön politiikkaan keskittyvä kolmas artikkeli osoittaa, että poliittisella päätöksenteolla voi olla merkittävä vaikutus toimialan muotoutumiseen ja alalla työskentelevien työoloihin. Se, miten hyvinvointivaltiot säätelevät (tai eivät säätele) palkatun kotitaloustyön markkinoita, heijastuu myös kotitaloustyöntekijöiden asemaan työmarkkinoilla. Eriarvoisuuden kerrostumat, rakenteellinen, yksilöön kohdistuva ja poliittinen, risteävät tavalla joka pitää kotitaloustyön ”erityisenä” alana kaikkialla maailmassa: kotityön kulttuurisesti vähäisempi arvostus yhdessä alan nais- ja maahanmuuttajavaltaisen työvoiman kanssa asettavat kotitaloustyöntekijät suurempaan riskiin työskennellä epävarmoissa työoloissa. Monissa maissa riittämätön hoivapalveluiden tarjonta ja kotitaloustyön heikomman aseman yleinen hyväksyntä kannustaa kotitalouksia kääntymään yksityisten kotitalous- ja hoivapalveluiden puoleen – mikä tarkoittaa usein epävirallisen työn teettämistä heikoilla työehdoilla. Kotitaloustyön prekaarius on kytköksissä moninaisesti eriarvoisessa asemassa oleviin sosiaalisiin kategorioihin, joita alalla työskentelevät edustavat. Paradoksaalisesti syyt henkilöiden eriarvoiselle asemalle (sukupuoli, ”rotu”, luokka, kulttuurinen tausta tai kansallisuus) ovat usein samat kuin alun perin heidän palkkaamiselleen. Kotitaloustyöntekijöiden palkkaan ja työehtoihin liittyvä keskustelu on haastavaa, sillä kyse on myös kotitalouksien kyvystä maksaa palveluista. Erityisesti maissa joissa kotitaloustyöntekijät työskentelevät kokopäiväisesti ja palkattu kotitaloustyö paikkaa hoivatarpeiden aukkoja, valtion tuen puuttuminen asettaa valtavia haasteita niin palveluita ostaville kotitalouksille kuin palveluita tarjoaville henkilöille. Kotitaloustyön ”uuden tulemisen” aikakautena, kun ala on vahvasti kytköksissä globalisaatioon ja myös tärkeä osa uusliberaalia hoivajärjestelmää, kotitaloustyöntekijöiden asemaa ja työehtoja koskevat kysymykset nousevat taas ajankohtaisiksi.